2020
DOI: 10.21608/ejabf.2020.91119
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal, biochemical and physiological effects of acetamiprid and thiamethoxam against Culex pipiens L. (Diptera: Culicidae).

Abstract: Mosquito control is the most common health problem facing many poor developing countries especially the transmitted diseases by mosquitoes (Deepak et al. 2019). Mosquitoes transmit many pathogens which cause dangerous diseases like Zika virus, filariasis, Japanese encephalitis, chikungunya, yellow fever, dengue, and malaria; that pose a real danger not only to human health (Santhosh et al. 2015; Vinoth et al. 2019) but also, extend their impact on the economy worldwide (Abutaha et al. 2018). Culex pipiens L. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
12
1
Order By: Relevance
“…Lotfy and Embaby (2020) reported a significant increase in the GST level in Spodoptera littoralis larvae after 24 hours post-treatment with thiacloprid neonicotinoids. Also, Abdel-Haleem et al (2020) found a significant elevation of the GST level in Culex pipiens larvae treated with thiamethoxam or acetamiprid.…”
Section: Discussionmentioning
confidence: 83%
“…Lotfy and Embaby (2020) reported a significant increase in the GST level in Spodoptera littoralis larvae after 24 hours post-treatment with thiacloprid neonicotinoids. Also, Abdel-Haleem et al (2020) found a significant elevation of the GST level in Culex pipiens larvae treated with thiamethoxam or acetamiprid.…”
Section: Discussionmentioning
confidence: 83%
“…The first phase is the cleavage of the substrate or addition of a polar group, while the second phase is the addition of sulfate, phosphate groups, sugar, or amino acid to the resulted products of 1st phase to increase hydrophilicity, consequently, facilitate excretion by the insect 41 . The most important enzymes responsible for the detoxification of toxins are CYP-450 for oxidative degradation and CarE for hydrolytic degradation that involved in 1st phase 42 . The detoxification capabilities of enzymes could be modified due to variations in gene expression 43 , consequently, variation of insect response to toxins 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The emerged adults were fed on 10% sucrose solution then females allowed for blood meal using a pigeon. All the experiments were held under controlled laboratory conditions at 27 ± 2 °C, 70 ± 5 % RH, and a 14:10 h light/dark photoperiod ( Abdel-Haleem et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%